2010
DOI: 10.1089/ten.tec.2009.0374
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Hepatic Failure in Mice by Transplantation of Mixed Microencapsulation of Rat Hepatocytes and Transgenic Human Fetal Liver Stromal Cells

Abstract: Microencapsulation-mediated cell therapy overcomes the immune incompatibility between donor and recipient in transplantation. The aim of this study was to investigate the effects of transplantation of microcapsules containing a mixture of rat hepatocytes and human fetal liver stromal cells (hFLSCs), engineered to produce basic fibroblast growth factor (bFGF), on acute liver failure (ALF) in mice. In vitro experiments showed that different combinations of microencapsulated rat's hepatocytes and stromal cells su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…In animal models, serum albumin decreased after acute liver failure induction, but stably returned to normal level when microencapsulated hepatocytes are transplanted [50]. This therapeutic effect, associated to a better survival rate, can be enhanced by transplantation of co-microencapsulated hepatocytes and islets of Langerhans, human umbilical vein endothelial cells or stromal cells [51], [52].…”
Section: Discussionmentioning
confidence: 96%
“…In animal models, serum albumin decreased after acute liver failure induction, but stably returned to normal level when microencapsulated hepatocytes are transplanted [50]. This therapeutic effect, associated to a better survival rate, can be enhanced by transplantation of co-microencapsulated hepatocytes and islets of Langerhans, human umbilical vein endothelial cells or stromal cells [51], [52].…”
Section: Discussionmentioning
confidence: 96%
“…Microencapsulation of cells as a useful technique for the delivery of bioactive molecules in vivo has been applied successfully in allogeneic or xenogeneic cell implants for several diseases, such as diabetes, liver failure and hypoparathyroidism [17,20,23]. The main advantage of microcapsules is to protect cells from a host’s immune system [24,25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Microencapsulation using alginate hydrogel has been widely used to overcome immune rejection and prevent the need for immunosuppressive therapy [17,18,19]. Although there is a physical separation of the transplanted cells from the host, small molecules such as erythropoietin and fibroblast growth factor can easily pass through the alginate gel barrier [20,21]. In a previous study, we have shown that met-enkephalin and norepinephrine in the CSF significantly increased following intrathecal implantation of microencapsulated PC12 cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therapies relying on microencapsulated cells could therefore result in the reduction or even avoidance of the administration of immunosuppressive drugs on the one hand and, on the other hand, permit the transplantation of non-human cells, which is a promising alternative considering the limited availability of donor organs [6,7]. The therapeutic potential of the transplantation of microencapsulated cells has been reported for the treatment of a variety of diseases, including liver failure [8][9][10], renal failure [11][12][13], cancer [14], and diabetes mellitus [15][16][17][18].…”
Section: Cell Microencapsulationmentioning
confidence: 99%